Safety Performance Analysis for Traffic Management During Activation and Deactivation Lane Closure at Highway New Klang Valley Expressway (Nkve) - A Ramlan, Danish Akmal (Progress in Engineering Application and Technology, 2023)
Highway maintenance keeps drivers safe and comfortable. Routine maintenance of pavement, road shoulder, slope, and other assets should also be done. MHA has established uniform guidelines for lane closures on highways as well as standard techniques for traffic control schemes on all Malaysian highways, namely "Traffic Management Plan Guidelines," in order to perform maintenance on important highway routes. Descriptive analysis was used to analyse information on activation and deactivation lane closure. The statistical analysis was conducted on the overall hazard base on descriptive statistics. Based on the data obtained injuries that often happen to workers are injuries to the right leg with a high medical certificate throughout the 5 years from 2017 to 2021. The highest frequency of accidents is in 2019 for all types of graphs. Overall, objectively identify the hazards, analyze the accidents involving before, after and during activation and deactivation of lane closure during work at highway New Klang Valley Expressway (NKVE) determine the category of traffic accidents against workers that are coded as the most critical in the accident data company.